Antioxidant Properties of S-Nitrosoglutathione and Nanotechnologies - Marianne Parent; Yi Zhou; Justine Bonetti; Caroline Perrin-Sarrado; Isabelle Lartaud; Anne Sapin-Minet; Caroline Gaucher (Proceedings, 2019)
Cardiovascular diseases are associated with oxidative stress and a reduced bioavailability of nitric oxide (NO). To counteract both processes, the administration of S-nitrosoglutathione (GSNO) can be envisaged. GSNO is able to induce protein S-nitrosation (Pr-SNO), which is a post-translational modification of proteins, participating in the storage of NO in tissues, and protect thiol functions from oxidation. However, GSNO antioxidant power is poorly studied, which is probably linked to its low stability. This low stability can be addressed by nanotechnologies that will increase GSNO protection and provide a sustained release of the drug.